Chemical coagulants and Moringa oleifera seed extract for treating concrete wastewater - Paula, Heber Martins de; Ilha, Marina Sangoi de Oliveira; Andrade, Leonardo Santos (Acta Scientiarum. Technology, 2016)
Wastewater from concrete plants has a high pH and a high concentration of suspended solids, necessitating treatment before reuse or discharge into the environment. The objective of this study is to evaluate the efficiency of two chemical coagulants, aluminum sulfate (Al2(SO4)3) and iron chloride (FeCl3), and a natural coagulant, Moringa oleifera (MO), all in their soluble forms, in the treatment of wastewater from concrete plants. To this end, the efficiencies of the three coagulants, in combinations with different proportions, were tested. The quality parameters of the wastewater obtained after the treatments were compared to the limit values for non-potable water. The use of coagulants in their soluble form potentiates their effect, especially when preparing the MO extract, i.e., greater amounts of the protein responsible for the coagulation is extracted. A mixture with MO and Al2(SO4)3 in a 20:80 proportion showed the best results, with 97.5% of the turbidity removed at 60 min. of sedimentation, allowing the treated water to be used for washing vehicles and flushing toilets. The FeCl3 treatment produced a high concentration of chlorides, which could cause corrosion problems, and is therefore not recommended for concrete wastewater treatment. Â